Taking a Detour: Affective Stimuli Facilitate Ultimately (Not Immediately) Compatible Approach–Avoidance Tendencies - Reichardt, Regina (Frontiers in Psychology, 2018)
Abundant evidence suggests that affective stimuli automatically trigger responses that lead to a compatible change in distance between the affective stimulus and the self (positive í approach, negative í avoidance). A special situation arises, when a barrier blocks the direct way towards or away from an affective stimulus. Recent evidence suggests that in such cases affective stimuli facilitate responses that ultimately lead to a compatible change in distance, even when this requires an initial step in the opposite and thus incompatible direction. The present study investigated whether this is the case even when relatively complex processing is required to recognize the presence of a barrier and, thus, the need for a detour. Employing a stimulus-response-compatibility task, we asked participants to move a manikin along the pathways of a maze towards or away from a positive or negative stimulus. The direct way was possible on half of the trials and blocked by a barrier on the other half of the trials. In the latter case, the manikin had to first be moved in the direction opposite to the position ultimately intended. We manipulated between participants the type of barrier and, thus, the complexity of cognitive processing required to recognize the need for a detour. In the simple condition, a black bar was presented as a barrier on the way. In the complex condition, a blue or yellow bar was presented, and the color indicated whether the bar constituted a barrier (locked gate) or not (open gate). Replicating and extending previous findings, the present study shows that affective stimuli facilitate ultimately (not immediately) compatible approach-avoidance responses, even when relatively complex processing is required to recognize the need for a detour.